Epidemiological aspects, diagnosis and treatment for brazillian spotted fever group rickettsiosis (Research, Society and Development, 2021)
Rocky Mountain spotted fever is an uncommon febrile illness and was first characterized in North America around the end of the 19th century. This disease is caused by the bite of the star tick, of the species Amblyomma cajennense, infected with the gram-negative bacterium Rickettsia rickettsii. This vector, the tick belongs to the Ixodidae family, are hematophagous, preferring wild animals, especially horses and rodents, such as capybaras. The incidence of spotted fever is greatest during the winter season and the first days of spring. Therefore, residents of areas closer to forests and gardens with the presence of animals possibly carrying ticks should be careful not to become infected with spotted fever. For contagion by this bacteria, long-term contact between the tick and man is necessary. This disease progresses with various signs and symptoms that can appear within 2 days to 2 weeks after the bite of a tick infected with Rickettsia. Treatment must be started within 5 days after the onset of symptoms and is carried out through antibiotic therapy, in order to avoid more serious complications that could arise without starting treatment. This study is an integrative review of spotted fever, aiming to characterize the disease and its aspects on epidemiology, diagnosis and treatment.